A Foresight Study on Utilising AI Infrared Camera on Smartphone to Fully Digital Quality Assessment of Vegetables and Fruits Freshness Among Malaysian Farmers - Tay YX, Adeline; Kamaruddin, Nor Kamariah (Research in Management of Technology and Business, 2025)
Artificial Intelligence (AI) is one of the mechanisms used to detect and read signals or obtain information that humans could not acquire directly. AI infrared cameras can be attached to smartphones that act as a tool to access the usage of infrared cameras. The purpose of this study is to identify the issues, challenges, and trends of utilising AI infrared cameras on smartphones for a fully digital quality assessment of vegetables and fruits among Malaysian farmers. This research also discusses key drivers and the future image of using AI infrared cameras on smartphones to fully digital quality assessment of vegetables and fruits among Malaysian farmers. The target respondents selected are government agencies related to the agriculture sector, and farmers, who consist of 384 respondents. This research utilized foresight instruments such as STEEPV analysis and SPSS analysis. Eight merged key drivers have been identified in this study. SPSS is used to show the results of key drivers and the second research phase with impact-uncertainty analysis. The top two drivers are sustainable and technological advancement. 384 questionnaires were distributed online, and the return rate was 16.15%. The scenario analysis has been formed with the top two drivers, and four scenarios represent the possible future image from 2024 to 2034. Hence, this research aims to help future researchers create awareness of utilising AI infrared cameras in the agriculture sector. A further explanation of the findings is provided below.